2022
DOI: 10.7759/cureus.27767
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis a Cause of Cardiovascular Diseases: A Review Article

Abstract: Psoriasis is a severe, chronic inflammatory disease characterized by erythematous plaques across the extensor surfaces of the skin. Psoriasis has been linked to a higher threat of vascular events like myocardial infarction and stroke. Other associated cardiovascular disorders in the case of psoriasis include building up atherosclerosis, non-ischemic dilated cardiomyopathy, and psoriatic arthritis. Individuals can use International Classification of Diseases (ICD-9) codes to identify cardiovascular disease/como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Our results indicated that patients with PsD have an increased risk of stroke. Published work has suggested a relationship between stroke and psoriasis via in ammatory processes 31 . This is in line with our knowledge that in ammation is a well-known cardiovascular disease risk factor 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that patients with PsD have an increased risk of stroke. Published work has suggested a relationship between stroke and psoriasis via in ammatory processes 31 . This is in line with our knowledge that in ammation is a well-known cardiovascular disease risk factor 7 .…”
Section: Discussionmentioning
confidence: 99%